Formation of Tubular Aluminum Oxides by Local Electrochemical Anodization in Organic Electrolytes and Their Anti-Reflection Properties - S. K. Lazarouk; V. V. Dudich; T. I. Orekhovskaya; D. A. Sasinovych; L. P. Tomashevich; A. A. Ustimenko; A. A. Povzhik; N. A. Kalanda; D. A. Symonenko; S. M. Ivanyuta (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Research has been carried out on the formation of tubular aluminum oxides by local electrochemical anodization in aqueous solutions of organic acids such as formic, citric, tartaric, malic and others. Self-ordered nanostructures formed this way can be used in the manufacture of various optical devices. Tubular aluminum oxides formed by local electrochemical anodization in organic acids have a high concentration of anionic complexes containing carbon atoms over 10 at.%. Studies of reflection spectra showed effective anti-reflection properties of films with a specular reflection coefficient of 0.7–1.4 %.